Do European co-residential caregivers aged 50+ have an increased risk of frailty? - Barbosa, Fátima (2020)
One important health challenge associated with ageing is frailty, which has been acknowledged as a new public health priority. However, only a few studies have explored the relationship between providing care at older ages and frailty. The main objective of this study is to assess whether there is an association between providing co-residential care and frailty, according to gender and from a European cross-sectional perspective, among the population aged 50+. Data from 17 European countries that participated in wave 6 of the Survey of Health, Ageing and Retirement in Europe (SHARE) is used (N = 52,073). Multinomial logistic regressions were used to estimate caregivers' chances of frailty. The results show that the prevalence of pre-frailty and frailty differs according to the caregiver's status, gender and the European region. The highest prevalence of pre-frailty was found in the group of female caregivers from Northern countries (57.3%), and the highest prevalence of frailty was found in the group of female caregivers from Southern countries (29.3%). Providing co-residential care is positively associated with the risk of being pre-frail in women, in all European regions (Northern: OR 1.724, 95% CI 1.190-2.496; Central: OR 1.213, 95% CI 1.010-1.456; Eastern: OR 1.227, 95% CI 1.031-1.460; Southern: OR 1.343, 95% CI 1.103-1.634), and with being frail for both genders in the Southern region (female: OR 1.527, 95% CI 1.060-2.200; male: OR 1.644, 95% CI 1.250-2.164). The results of this study suggest that female co-residential caregivers are a greater risk of being pre-frail in all European regions except Southern Europe, where male and female co-residential caregivers are a greater risk of being frail, compared with non-caregivers. European policy makers should create political measures to prevent and reverse frailty among European co-residential caregivers.